2006
DOI: 10.1017/s0031182006001211
|View full text |Cite
|
Sign up to set email alerts
|

A case of mistaken identity – reappraisal of the species of canid and felid hookworms (Ancylostoma) present in Australia and India

Abstract: This study serves to clarify the current status of canid and felid Ancylostoma species present in Australia. The morphological identification of A. ceylanicum from cats for the first time in Townsville, Australia, appears to be in error, together with the genetic markers provided for the species. Morphological and genetic data presented herein provide strong evidence that the hookworms from cats in Towsville are not A. ceylanicum as previously identified (i.e. the first report of this species in Australia), bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…The dingo was probably introduced 4000 years ago, but the parasites that accompanied it are unknown (Beveridge, 2002). It was puzzling that A. ceylanicum had not been found previously in Australia given that A. braziliense, A. caninum and A. tubaeformehave all been recovered from Australian dogs and cats in the past (Traub et al, 2006). Furthermore, the absence of A. ceylanicumfrom northern Australia was intriguing given the endemic distribution of this parasite in neighbouring regions: Malaysia (Yoshida et al, 1973;Sheikh et al, 1985), Borneo (Choo et al, 2000), Indonesia (Margono et al, 1979), Papua New Guinea (Anten and Zuidema, 1964) and the Solomon Islands (Beveridge, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dingo was probably introduced 4000 years ago, but the parasites that accompanied it are unknown (Beveridge, 2002). It was puzzling that A. ceylanicum had not been found previously in Australia given that A. braziliense, A. caninum and A. tubaeformehave all been recovered from Australian dogs and cats in the past (Traub et al, 2006). Furthermore, the absence of A. ceylanicumfrom northern Australia was intriguing given the endemic distribution of this parasite in neighbouring regions: Malaysia (Yoshida et al, 1973;Sheikh et al, 1985), Borneo (Choo et al, 2000), Indonesia (Margono et al, 1979), Papua New Guinea (Anten and Zuidema, 1964) and the Solomon Islands (Beveridge, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was then isolated from the supernatant tubaeforme, A. ceylanicum, A. braziliense and U. stenocephala was amplified using previously published primers, PCR reaction, and cycling conditions (Traub et al, 2004). An amendment to this PCR was however recently made by Traub et al (2006) whereby it was recognized that the reference sequence of A. ceylanicum was in fact that of A. braziliense. Hence RTGHFI (5′-CGTGCTAGTCTTCAGGACTTTG-3′) and RTABCR1 (5′-CGGGAATTGCTATAAGCAAGTGC-3′) were used to amplify a 545 bp region of A. caninum, A. tubaeforme, A. ceylanicum and U.…”
Section: Dna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The advent of biomolecular techniques has shown that morphological criteria are not reliable enough to distinguish between different species of Ancylostoma larvae. 7 Therefore, this case is the first case of HrCLM in which a hookworm species could be identified by molecular techniques.…”
mentioning
confidence: 99%
“…Gastrointestinal helminthiasis is the most commonly encountered disease in dogs rearing across the globe including India (Traub et al 2007). Among the gastrointestinal helminths, both Ancylostoma spp.…”
Section: Introductionmentioning
confidence: 99%